Advances in Intelligent Information Hiding and Multimedia Signal Processing Proceedings of the Thirteenth International Conference on Intelligent Information Hiding and Multimedia Signal Processing, August, 12-15, 2017, Matsue, Shimane, Japan, Part II - Pan, Jeng-Shyang; Tsai, Pei-Wei; Watada, Junzo; Jain, Lakhmi C. (Smart Innovation, Systems and Technologies,, 2018)
This volume includes papers presented at IIH-MSP 2017, the 13th International Conference on Intelligent Information Hiding and Multimedia Signal Processing, held from 12 to 15 August 2017 in Matsue, Shimane, Japan. The conference addresses topics ranging from information hiding and security, and multimedia signal processing and networking, to bio-inspired multimedia technologies and systems. This volume of Smart Innovation, Systems and Technologies focuses on subjects related to massive image/video compression and transmission for emerging networks, advances in speech and language processing, information hiding and signal processing for audio and speech signals, intelligent distribution systems and applications, recent advances in security and privacy for multimodal network environments, multimedia signal processing, and machine learning. Updated with the latest research outcomes and findings, the papers presented appeal to researchers and students who are interested in the corresponding fields.